Evaluation of coconut (Cocos nucifera) for tender nut quality in Maidan tracts of Karnataka (Current Horticulture, 2024)
Evaluation of coconut (Cocos nucifera L.) varieties for growth and tender nut quality was carried out at Horticulture Research and Extension Centre (UHS, Bagalkot), Arsikere, Karnataka. The highest palm height (2.35 m) was recorded in Kalpa Dhenu, whereas it was lowest (1.22 m) in COD at the age of nine years. Palm girth (101.78) and leaf length (4.73 m) were maximum in variety Kalpatharu. Higher amount of tender nut water (605 ml/nut) in Kalpa Dhenu, whereas, Gautami ganga (551.7 ml/nut) and COD (520 ml/nut) had optimum quantiy of water. Gauthami Ganga recorded highest TSS (6.1°Brix) and lowest titrable acidity (0.05%). COD recorded maximum total sugars (6.79 g/100 ml) and lowest acidity (0.05%). Gauthami Ganga had optimum quantity of mineral content (61.47 mg/100 ml calcium, 10.87 mg/100 ml magnesium, 2023.33 ppm potassium and 23.33 ppm sodium). Organoleptic evaluation indicated that Gauthami Ganga (8.5) and COD (7.23) were the best for tender nut purpose as both of them ranked good for taste of water.
Keywords: Tender nut; Organoleptic; Mineral content; Plant height; TSS; Bevarage